Pendampingan Belajar Peserta Didik Menggunakan Media Pembelajaran Adventure of Algebra (AOA) dalam Menanamkan Nilai-Nilai Pancasila di MTsN Gowa - Muh. Aprizal Irawan; Fatmalasari; Susi Susanti; A. Sriyanti; Wahida Jamaluddin (Faculty of Tarbiyah and Teacher Training, 2024)
Bhineka tunggal Ika is a great strength and the foundation of the Republic of Indonesia. The development of the times must still be accompanied by the cultivation of the basic values of Pancasila, especially in terms of tolerance of diversity through character education. The purpose of this research is to create learning media that integrates the cultivation of the values of the third principle of Pancasila with mathematics lessons. Adventure Of Algebra (AOA) is a solution that can be used as a learning media that is not only able to increase students' interest and learning outcomes but can be a space to instill Pancasila values, especially in the third principle of Pancasila, namely Indonesian unity. The implementation of learning is carried out offline in class for 3 hours of learning. The learning stages carried out begin at the planning stage, pre-test, demonstration of the use of learning media, post-test, and evaluation. Based on the results of the pre-test, it shows that the learning outcomes of students in algebraic material obtained an average of 78 while regarding the results of direct observation of initial knowledge related to Pancasila values show that only about 45% of the total number of students in class IX.5 who understand well the values of Pancasila. Meanwhile, based on the results of the post-test of students, the average learning outcomes of students increased to 86. And for the results of observations related to the tendency of students to understand the values of Pancasila increased to 85% which is described in the learning process that takes place actively and fun for students. With an active and fun learning process, you also have to adjust the learning media used with the sub-materials that students learn.